2023
DOI: 10.1002/anie.202305558
|View full text |Cite
|
Sign up to set email alerts
|

Covalently Grafting Graphene onto Si Photocathode to Expedite Aqueous Photoelectrochemical CO2 Reduction

Abstract: Silicon semiconductor functionalized with molecular catalysts emerges as a promising cathode for photoelectrochemical (PEC) CO 2 reduction reaction (CO 2 RR). However, the limited kinetics and stabilities remains a major hurdle for the development of such composites. We herein report an assembling strategy of silicon photocathodes via chemically grafting a conductive graphene layer onto the surface of n + -p Si followed by catalyst immobilization. The covalently-linked graphene layer effectively enhances the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…The elemental mapping results (Figure j) show the distribution of MoS 2 on Si/rGO, and the corresponding energy-dispersive X-ray (EDX) spectrum (Figure S2) verifies that Si/rGO/MoS 2 is composed of Si, C, O, Mo, and S. As indicated in the infrared spectra (Figure a), a hydroxyl-rich Si surface can be obtained after Piranha solution treatment. A much stronger peak appears at about 3380 cm –1 , indicating more hydroxyl groups have been modified onto the Si surface after the esterification reaction . Raman spectra of Si/rGO/MoS 2 show characteristic peaks of rGO (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…The elemental mapping results (Figure j) show the distribution of MoS 2 on Si/rGO, and the corresponding energy-dispersive X-ray (EDX) spectrum (Figure S2) verifies that Si/rGO/MoS 2 is composed of Si, C, O, Mo, and S. As indicated in the infrared spectra (Figure a), a hydroxyl-rich Si surface can be obtained after Piranha solution treatment. A much stronger peak appears at about 3380 cm –1 , indicating more hydroxyl groups have been modified onto the Si surface after the esterification reaction . Raman spectra of Si/rGO/MoS 2 show characteristic peaks of rGO (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, it reached a maximum partial current density of −4 mA cm −2 at −0.4 V (vs. RHE) for CO generation. 99 Zheng et al reported the sequential fabrication of the p-Si/ n-ZnO v /p-Cu x O nanostructure using chemical methods, involving the replacement of Zn with Cu. The resulting p-Si/n-ZnO v / p-Cu x O structure demonstrated exceptional PEC CO 2 RR selectivity towards ethanol at low biases, achieving an outstanding FE of approximately 60% at 0 V vs. RHE.…”
Section: Co-catalyst Deposition Via Other Methodsmentioning
confidence: 99%
“…Additionally, it reached a maximum partial current density of −4 mA cm −2 at −0.4 V ( vs. RHE) for CO generation. 99…”
Section: Investigation Of Co-catalysts For Selective Co2 Reduction Re...mentioning
confidence: 99%
“…To further facilitate the charge transfer between Si and graphene, Wei et al grafted graphene directly onto the Si surface via covalent bonding thus avoiding the impediment of TiO 2 interlayer to the charge transfer. [53] The homogeneous catalyst cobalt tetraphenylporphyrin (CoTPP) was immobilized on the surface of graphene via π-π stacking interaction. An onset potential of ~0.1 V (vs. RHE) was finally achieved for PEC CO 2 reduction, with a maximum partial current density of ~À 4 mA cm À 2 at À 0.4 V (vs. RHE) for CO production.…”
Section: Si-based Photoelectrodes Pec Reduction Of Co 2 To Comentioning
confidence: 99%